The Cultural Politics of Youth, Health and Lifestyle in the Aftermath of the Childhood Obesity “Epidemic” - Stoneman, Scott (My University, 2012)
In this dissertation I argue that the currency of the childhood obesity “epidemic” as a health crisis is derived largely from processes of representation and reproduction through which fatness has been re-calibrated as something pathogenic. I develop the position that the “childhood obesity epidemic”—influenced as it is by neoliberal notions of what constitutes a healthy individual and a vital body politic—risks exacerbating, rather than mitigating, the vulnerability of children.
The methodology of this project uses the example of lifestyle to illustrate how consensus about the presence of an “obesity epidemic” has been built, the concept of lifestyle being read as representative of how particular constellations of anxiety regulate what counts as true in the developing body of social knowledge concerning childhood obesity. I contend that the problem of lifestyle captures the complexities of the “childhood obesity epidemic” because children are presupposed, in obesity discourses, to be more vulnerable to the sweeping set of social trends brought under the rubric of the “obesity epidemic” than adults.
In what follows, I investigate the rationale for anti-obesity through an investigation of a series of analogous clusters, cases of persuasive ideas borne out of the moral panics subtending childhood obesity. I ask what it means that the child’s diminished capacity for autonomous decision-making is considered to be especially critical in the face of popular culture’s media “bombardment.” More broadly, I focus on the delimiting effect that anti-obesity’s politicization of lifestyle has had on recent attempts to think through the articulation of health, consumerism, environment, and the government of risk.
Keywords: obesity; childhood; health; lifestyle; representation; Feminist Philosophy; Public Health; Visual Studies; Feminist Philosophy